Coat protein gene sequence of tobacco mosaic virus encodes a host response determinant. - Saito, T (1987)
The common strain and tomato strain of tobacco mosaic virus (TMV) are known to be closely related to each other. However, plants with the N' gene, such as Nicotiana sylvestris and Nicotiana tabacum L. cv. Bright Yellow, respond differently to infections by these viruses. In the N' plants, TMV-OM (common strain) spreads systemically with mosaic symptoms, whereas TMV-L (tomato strain) induces the necrotic response of plants, causing local lesions. To reveal the viral factor of TMV-L inducing the necrotic response, we have constructed several recombinant viruses between the two strains, in which TMV-L RNA was partly replaced by TMV-OM RNA. The recombinant viruses having the coat protein gene sequence of TMV-OM in place of TMV-L produced no necrotic local lesions but spread systemically with mosaic symptoms in the N' plants. On the other hand, the recombinant viruses having TMV-OM-derived sequences other than the coat protein gene sequence, and in which the coat protein gene sequence of TMV-L still remained, produced necrotic local lesions. These observations indicate that the viral factor of TMV-L responsible for the necrotic response of the N' plants is coded in the coat protein gene sequence.